Molecular epidemiology of hepatitis D virus circulating in Southwestern Nigeria - Opaleye, Oluyinka Oladele; Japhet, Margaret Oluwatoyin; Adewumi, Moses Olubusuyi; Omoruyi, Ewean Chukwuma (Virology Journal, 2023)
International journal Molecular epidemiology of hepatitis D virus circulating in Southwestern Nigeria. Vol 13, No .61, P. 8